WebView: uma ferramenta para construção de visões de fontes de dados da web - Alisson Rabelo Arantes (2001)
The huge amount of useful data available on the Web has brought to the database comunity new challenges to develop techniques and tools for the manipulation of such data. Thus, the notion of view as a mechanism for providing access to data of interest, regardless of their structure, origin, and form of storage, has been revisited for the Web context. In this work, we present an environment composed of a set of high-level tools that allow the fetching, extraction, integration, and refreshing of Web data. Using this environment, database designers can build and maintain locally materialized Web views by defining schemas for data integration from many distinct Web data sources and plans for refreshing the view contents.